Defect-induced magnetism in TiO2: An example of quasi 2D magnetic order with perpendicular anisotropy - Stiller, Markus; Esquinazi, Pablo D. (Frontiers in Physics, 2023)
Magnetic order at room temperature induced by atomic lattice defects, like vacancies, interstitials, or their pairs, has been observed in a large number of different non-magnetic hosts, such as pure graphite, oxides, and silicon-based materials. High Curie temperatures and time-independent magnetic response at room temperature indicate the extraordinary robustness of this new phenomenon in solid-state magnetism. In this work, we review experimental and theoretical results of pure TiO2 (anatase), whose magnetic order can be triggered by low-energy ion irradiation. In particular, we discuss the systematic observation of an ultrathin magnetic layer with perpendicular magnetic anisotropy at the surface of this oxide.